The Influence of 21st Century Skills On Readiness Career Of Accounting 4.0 - Eren Prinstin; Endang Sri Andayani; Dodik Juliardi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The Industrial Revolution 4.0 is marked by technological advances in various fields, such as artificial intelligence, supercomputers, smart robots, cloud computing, big data systems, and genetic engineering that allows humans to further optimize brain function. Industrial revolution 4.0 is predicted to have a significant and extraordinary impact on various aspects, especially on products, supply chains, consumers, and workers. Accountants are one of the workers or professions that are disrupted. In preparing for their careers, accountants should prepare themselves by honing soft skills and be able to adapt to changes that occur, so that the 4.0 revolution is not a challenge but an opportunity in the future. Soft skills that will be discussed in this study refer to 21st-century skills. 21st-century skills are divided into learning skills, literacy skills, and life skills. This study uses a closed survey instrument, this study collects data from four universities in Malang City. The research hypothesis was tested using Structural Equation Modeling (SEM) with Smart Partial Least Square (Smart-PLS). The data analysis used in this research is the outer model (measurement model) and the inner model (structural model). The results showed that learning skills, literacy skills, and life skills affected students' readiness for careers to become accountants 4.0. Gender and education programs also show an influence on students' readiness for careers to become accountants 4.0